Dynamically Normalized Pupillometry for Detecting Delayed Cerebral Ischemia After Aneurysmal Subarachnoid Hemorrhage - Julian Klug, MD; Joana Martins, MD; Ignazio De Trizio, MD; Emmanuel Carrera, MD; Miodrag Filipovic, MD; Isabel Charlotte Hostettler, MD, PhD; Urs Pietsch, MD (Critical Care Explorations)
OBJECTIVES:. Delayed cerebral ischemia (DCI) is a major driver of morbidity after aneurysmal subarachnoid hemorrhage (aSAH). Quantitative pupillometry has been shown to be of prognostic value after acute neurological injury. However, the evidence for the use of pupillometric features for the detection of DCI has been conflicting. The aim of this study was to investigate the prognostic value of frequent pupillometric monitoring for DCI detection. DESIGN:. Observational cohort study from a prospective aSAH registry. SETTING:. Tertiary referral center. PATIENTS:. Adult patients with confirmed aSAH admitted to the ICU between March 2019 and December 2023. INTERVENTIONS:. None. MEASUREMENTS AND MAIN RESULTS:. One hundred fourteen patients were included, of which 31 (27.2%) suffered from DCI. All patients underwent frequent pupillometry (every 3 hr). We determined the absolute value of the neurological pupil index (NPi) and constriction velocity (CV), and their value normalized to the maximal recorded value between the admission and the pupillometry measure to account for personalized baselines. The association between pupillometry values and the occurrence of DCI within 6–24 hours was investigated. Normalized CV had the best discriminative performance to identify DCI within 8 hours, with an area under the receiver operating characteristic curve of 0.82 (95% CI, 0.69–0.91). NPi, as well as non-normalized metrics, were not significantly associated with DCI. CONCLUSIONS:. Normalized CV has a clinically and statistically significant association with the occurrence of DCI after aSAH. Frequent quantitative pupillometry could improve the multimodal monitoring of patients after aSAH with the goal of improving the identification of patients likely to benefit from therapeutic interventions.